Predicting the Specificity- Determining Positions of Receptor Tyrosine Kinase Axl - Karakulak, Tülay; Rifaioglu, Ahmet Sureyya; Rodrigues, João P. G. L. M.; Karaca, Ezgi (Frontiers in Molecular Biosciences, 2021)
Owing to its clinical significance, modulation of functionally relevant amino acids in protein-protein complexes has attracted a great deal of attention. To this end, many approaches have been proposed to predict partner-selecting amino acid positions in evolutionarily close complexes. These approaches can be grouped into sequence-based machine learning and structure-based energy-driven methods. In this work, we assessed these methods' ability to map the specificity-determining positions of Axl, a receptor tyrosine kinase involved in cancer progression and immune system diseases. For sequence-based predictions, we used SDPred, Multi-RELIEF, and Sequence Harmony. For structure-based predictions, we utilized HADDOCK refinement and molecular dynamics simulations. As a result, we observed that (i) sequence-based methods overpredict partner-selecting residues of Axl and that (ii) combining Multi-RELIEF with HADDOCK refinement-driven predictions provides the key Axl residues, covered by the extensive molecular dynamics simulations. Expanding on these results, we propose that a combined sequence-structure-based approach is necessary to determine specificity-determining positions of Axl, which can guide the development of therapeutic molecules to combat Axl misregulation.